A comparison of the actions of different bronchodilators in asthma. Issue 6 (November 1968) - Freedman, Bernard J.; Meisner, Peter; Hill, G. B.
Abstract : The actions of the following pressurized bronchodilators were compared by administration to 24 asthmatics: (1) Medihaler Iso Forte, (2) Alupent, (3) Medihaler-duo, (4) Bronchilator, and (5) Prenomiser Plus. These contained one or more of the following: isoprenaline, orciprenaline, isoetharine, phenylephrine, atropine methonitrate, and thenyldiamine. The dose was a single discharge from the container. The response was assessed by calculating the mean percentage change in F.E.V. at intervals after inhalation. The mean peak rises were respectively (1) 49·4%, (2) 43·6%, (3) 36·2%, (4) 33·5%, and (5) 23·5%. The amplitude of peak response to isoprenaline was related to the logarithm of the dose. Weight for weight, orciprenaline had a peak bronchodilator activity 41·5% that of isoprenaline and isoetharine 50%. The preparations did not differ significantly in the time taken to reach maximum response, which varied from 5 to 60 minutes; three-quarters of the maxima occurred within 15 minutes. The half-life for Alupent was 2 hours; for Medihaler-duo, which contains 240 μg. of phenylephrine per dose, it was 1¼ hours; for the remaining preparations it was about 1 hour. The decay rate, after the first half-hour, was 6% of the basal F.E.V. per hour for Medihaler-duo; for the other preparations it was 10-12%. In the doses given, Alupent yielded 20% and 30% increases lasting 130 and 67 minutes; after Medihaler Iso Forte these lasted 78 and 46 minutes. Similar comparative experiments, designed to eliminate effects of dosage difference, are desirable. Rebound bronchoconstriction occurred in 23% of 92 experiments. There was no response to propellent alone. The mean percentage change in F.E.V. may not be the best way of expressing results.